Consensus Ecclesiae: Aquinas on the Real and Apparent Unity of the Church - Roszak, Piotr; Berry , John (De Medio Aevo, 2025)
Current sociological and theological observations point to the existence of a phenomenon known as “de-churching” in Western countries. Within the Church, there has been a long-standing discussion on the relativisation of some points of the doctrine and the dilution of the notion of consensus in the Church in favour of what could even be described as deliberate multiplicity that does not need to be reconciled. In this perspective, I would like to analyse Aquinas’s teaching about the consensus Ecclesiae, a theme which opens up the wider subject of the unity of and affiliation with the Church. Aquinas analyses the notion of ecclesial consensus and the unity/multiplicity relationship – concerning, for instance, opinions on the truths of the faith, permissible divergences, or “differences” in faith – in the context of unity with Christ and the concept of the persona mystica. This implies an alignment of the members with the Head, a constant movement of reconciliation that takes place not so much among the members as it does between them and Christ. In this sense, the “wounds of unity” in the form of heresies and schisms and the dangers that stem from them occupy his attention in many commentaries in which he makes an effort to demonstrate errors. This pursuit of unity is more than a concordance of opinions; it is an ontological perseverance in communion with Christ. Aquinas’s reflections on the unity of the Church in the historical dimension will be presented in this light, with his distinction between implicit and explicit faith.